Incidência de reações adeversas a medicamentos em hospital de ensino no nordeste do Brasil - Gomes, Adriana Parente (2004)
Adverse drug reactions (ADR) constitute cause of morbidity in hospitalized patients, represent a risk for patients and an increase in the period patients stay in hospitals and the costs. OBJECTIVES: To determine the incidence of adverse drug reactions in the Walter Cantídio University Hospital (WCUH), investigate what factors may be associated with these events and propose measures to prevent or reduce the negative impact of those reactions. METHODS: An observational, analytical, and prospective study, with intensive monitoring of patients, analysis of the cumulative incidence of ADR and an exploratory evaluation of its determinants. The study included all inpatients in the medical clinics of WCUH from September 1st, 2000 to February 28th 2001, which were assisted from admission until discharge or death, to detection and monitoring of adverse reaction. Daily calls were made to the clinics WCUH in order to register the use of drugs and the occurrence of ADR. Cases in which patients had ADRs were assessed according to the methodology proposed by the World Health Organization. The reactions were classified based on liability, severity and type. Drugs were classified according to the Anatomical-Therapeutical-Chemical (ATC), Classification Index and adverse reactions through the WHO-ART also recommended by the World Health Organization. RESULTS: 970 patients were admitted to the medical clinics of HUWC. Of those, 54% were women and 46% were men, ranging in age from 09 months to 97 years. All patients received medication during hospitalization, ranging from 1 to 20 drugs / patient. The most commonly used drug groups (1st level ATC) are drugs that act on central nervous system (19.0%), drugs that act on the digestive tract and metabolism (17.0%), and drugs that act on the cardiovascular system (16.7%). Of the total, in eight (8%) the diagnosis for admission was an adverse reaction to medication. During the study, 30 new cases of ADRs in inpatients were registered. The results of adverse reactions comprised mainly skin disorders (65.0%) and general disturbances (25.0%). About gravity, the reactions were mostly classified as moderate (79.0%), followed by mild reactions (19.0%). The relation of causality was considered probable in 58.0% of cases and set at 24.5%. Most involved pharmacological groups were antibiotics for systemic use (66.4%), followed by drugs that act on the nervous system (7.7%), antineoplastic and immunomodulating agents (7.7%). The incidence of ADR among inpatients is not associated with age or gender. The number of days of hospital admission interfered with the occurrence of RAM. CONCLUSION: Adverse reactions as cause of admission were identified. All inpatients with ADRs have skin manifestations. Antibiotics, especially cephalosporins, were drugs commonly involved with the occurrence of ADRs in inpatients.